Chile : Report on Observance of Standards and Codes(ROSC) Data Module. (IMF Staff Country Reports; Country Report ;, 2001)
This paper is a summary assessment of Chile's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS) complemented by an in-depth assessment of the dimensions of data quality for the national accounts, prices, government finance, monetary, and balance-of-payments statistics. The Chilean agencies that produce these sets of statistics are the National Statistics Institute (INE), the Central Bank of Chile (BCCH), and the Ministry of Finance (MOF). Chilean statistics are generally relevant, timely, and frequent, and otherwise meet users' needs.